2021
DOI: 10.3389/fonc.2021.676626
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative nTMS and Intraoperative Neurophysiology - A Comparative Analysis in Patients With Motor-Eloquent Glioma

Abstract: BackgroundThe resection of a motor-eloquent glioma should be guided by intraoperative neurophysiological monitoring (IOM) but its interpretation is often difficult and may (unnecessarily) lead to subtotal resection. Navigated transcranial magnetic stimulation (nTMS) combined with diffusion-tensor-imaging (DTI) is able to stratify patients with motor-eloquent lesion preoperatively into high- and low-risk cases with respect to a new motor deficit.ObjectiveTo analyze to what extent preoperative nTMS motor risk st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…The treating neurosurgeon decided about using intraoperative neuromonitoring (IOM) to ensure the integrity of the motor system based on a previously published risk stratification ( 21 , 22 ). Warning criteria were a decrease in MEP amplitudes >50% and a subcortical stimulation intensity <5mA which we described in detail elsewhere ( 23 ). No awake craniotomies were performed in this series.…”
Section: Methodsmentioning
confidence: 99%
“…The treating neurosurgeon decided about using intraoperative neuromonitoring (IOM) to ensure the integrity of the motor system based on a previously published risk stratification ( 21 , 22 ). Warning criteria were a decrease in MEP amplitudes >50% and a subcortical stimulation intensity <5mA which we described in detail elsewhere ( 23 ). No awake craniotomies were performed in this series.…”
Section: Methodsmentioning
confidence: 99%
“…Another advantage is that the preoperative nTMS risk stratification facilitates the IOM (e.g. determining the subcortical stimulation intensity or interpreting heterogeneous phenomena such as a transient decrease of MEP amplitude) ( Rosenstock et al, 2021b ). In summary, recent studies showed several benefits for nTMS motor mapping and tractography, so patients with motor-eloquent brain tumors should ideally be treated at centers with experience in these techniques ( Ille and Krieg, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor resections in motor eloquent regions were performed only by neurosurgeons with extensive experience in the field of neuro-oncologic surgery. Intraoperative neuromonitoring (IOM) such as transcranial motor evoked potentials and/or subcortical stimulation via the surgical aspirator took place if the distance of the tumor to the pyramidal tract was less than 1 cm ( Rosenstock et al, 2021b ). No awake surgeries were performed.…”
Section: Methodsmentioning
confidence: 99%
“…Other preoperative tools have gained popularity in recent years, such as the preoperative transcranial magnetic stimulation (TMS) (71)(72)(73)(74)(75)(76). As a future perspective, our team aims at evaluating and validating the preoperative TMS as a useful tool to improve reduced invasiveness and reliable negative mapping.…”
Section: Discussionmentioning
confidence: 99%